Treatment of pneumonia in young calves with orally administered Tylosin - ΣΑΡΡΗΣ, Κ.; ΑΝΔΡΕΩΤΗΣ, Ι.; ΚΥΡΙΑΚΗΣ, ΣΠ.; ΤΣΑΛΤΑΣ, Κ.; ΠΑΠΑΘΕΟΔΩΡΟΥ, ΑΘ.; ΛΕΟΝΤΙΔΗΣ, ΣΩΤ. (Journal of the Hellenic Veterinary Medical Society, 2019)
An experiment involving 40 imported 10-day old male calves was conducted in Greece to evaluate the effectiveness of orally administered tylosin tartrate at a daily dose of 2g per head in the milk replacer for 14 days, for the control of naturally occuring pneumonia. Positive control animals were individually injected with spectinomycin, Oxytetracycline and/or trimethoprin- +suplhadiazine. Tylosin treated calves had returned to health faster, and in the same group the Average Daily Gain (A.D.G) and Feed Conversion Ratio (F.C.R) were significantly (P<0.05) improved by 24% and 16.5% respectively in comparison with the controls. Several mycoplasma species were isolated from nasal swabs from 15 calves at the beginning of the experiment for the first time in Greece. Also E.coli strains were isolated from the faeces of all the animals on trial, but only in four calves 2 enteropathogenic serotypes were found.